PENGARUH APLIKASI PUPUK KANDANG AYAM CAIR TERHADAP PERTUMBUHAN TANAMAN KACANG TANAH (Arachis hypogea L.) PADA LAHAN GAMBUT DI DESA TETAP JAYA KECAMATAN MARBAU KABUPATEN LABUHANBATU UTARA - Badrul Ainy Dalimunthe (JURNAL AGROPLASMA, 2018)
Effect of application of liquid chicken manure on the growth of peanut plants (Arachis hypogeaeL) in peatlandas of Tetap Jaya Village, Marbau District, Labuhanbatu Utara Regency. This research was conducted in May until July 2017. The research method used was average. The data obtainedwere from plant height (cm), number of leaves (strands), and stem diameter (mm). Then the data is averaged. The result show that with the application of liquid manure fertilizer, the growth rate plants is faster than without the application of liquid manure. In the treatment application of liquid manure fertilizer showed a high average yield (16,60 cm), leaf valume (37,30 helai), stem diameter (5,56 mm) and without treatment applied liquid manure fertilizer showed high average yield (10, 99 cm), leaf volume (31,71 strands), and stem diameter (4,86 mm). The result show that the high growth of plants, leaves, and diameter of peanut tree treated with poultry manure application, the growth rate faster than that without the use of liquid manure application. Keywords :  Peanut plants (Arachis hypogeae. L.), Liquid chicken manure, peat land